Avaliação da atividade antimicrobiana do extrato hidroetanólico de Talisia esculenta Radlk - SALES JUNIOR, José Helvecio (2019)
The Talisia esculenta Raldk species is popularly known as pitomba. The plant is common in wet and dry forest areas from North to Northeast of Brazil and can be found easily in open markets or supermarkets and the trees that exist are naturally occurring. Pitomba has been studied due to the presence of phytochemical compounds that exert a series of biological activities, such as antioxidant activity. However studies with antimicrobial activity are scarce. Thus, it was investigated the action of the hydroalcoholic extract of the leaf of this species against strains of fungi and bacteria and also a mycobacterium aiming to develop a new therapeutic alternative (antimicrobial). The extract was prepared by macerating the plant material. The antioxidant activity was performed by the DPPH radical sequestration methodology. The microdilution technique was used to determine MIC and MBC. Cytotoxic activity was evaluated to reduce tetrazolium salt. The bioproducts developed were 5% anionic cream and 5% vaginal cream of the leaf extract, which was also evaluated for its antimicrobial activity. The chromatographic analysis identified phenolic acids and flavonoids such as quercitin and acacetin. The extract showed dose-dependent antioxidant activity, whose maximum percentage of activity for leaf extract was 18.41±0.18. The leaf extract tested at a concentration of 100mg/mL inhibited the growth of bacteria such as E. coli ATCC 25922, whose MIC was 25mg/mL. The extract also inhibited the growth of fungi, such as C. albicans ATCC 90028, whose MIC was 3.125mg/mL. Anionic 5% leaf cream also inhibited the growth of E. coli ATCC 25922, whose MIC was identical to that of the crude extract. Vaginal cream 5% of leaf extract also inhibited the growth of C. parapsilosis ATCC 22019. The extract and bioproducts were non-irritating to red blood cells as well as cell cultures tested (Macrophages RAW 264.7). The bioproducts showed no significant physical stability changes during the analyzed time periods (30 and 60 days). The pH presented value variation in the tested environments (refrigerator, greenhouse and environment), where the highest values were for the refrigerator environment. Thus, the extract and bioproducts have remarkable antimicrobial activity, as well as antioxidant action, do not have red blood cell irritant action, and are not toxic to the cells tested, proving the toxicological safety. Bioproducts were potentially viable in the development of new products for the treatment of infectious diseases and showed good physicochemical and microbiological stability.